2006
DOI: 10.1002/jlcr.1127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [18F]‐labeled N‐3(substituted) thymidine analogues: N‐3([18F]fluorobutyl) thymidine ([18F]‐FBT) and N‐3([18F]fluoropentyl) thymidine ([18F]‐FPT) for PET

Abstract: 1,4-Butane diol and 1,5 pentane diol were converted to their tosyl derivatives 2 and 3 followed by conversion to benzoate esters 4 and 5, respectively. Protected thymidine 1 was coupled separately with 4 and 5 to produce 6 and 7, which were hydrolyzed to 8 and 9, then converted to their mesylates 10 and 11, respectively. Compounds 10 and 11 were fluorinated with n-Bu 4 N[18 F] to produce 12 and 13, which by acid hydrolysis yielded 14 and 15, respectively. The crude products were purified by HPLC to obtain [ 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These studies primarily focused on the design, synthesis and biological evaluation of thymidine analogues with radiolabels at the N3-postion for cancer therapy and imaging (Figures 16 & 17). Alauddin et al reported the synthesis of a library of compounds with chloro-, bromo-, and iodo-substitutions at various positions of a N3-phenylalkyl side chain at thymidine (79–81) [86]. These agents may have been synthesized in preparation of a later synthesis of their radiohalogenated counterparts.…”
Section: Non-boronated N3-substituted Thymidine Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies primarily focused on the design, synthesis and biological evaluation of thymidine analogues with radiolabels at the N3-postion for cancer therapy and imaging (Figures 16 & 17). Alauddin et al reported the synthesis of a library of compounds with chloro-, bromo-, and iodo-substitutions at various positions of a N3-phenylalkyl side chain at thymidine (79–81) [86]. These agents may have been synthesized in preparation of a later synthesis of their radiohalogenated counterparts.…”
Section: Non-boronated N3-substituted Thymidine Analoguesmentioning
confidence: 99%
“…Relative TK1 phosphorylation rates for some compounds of this series ranged from 2–6% [26]. Members of the research teams of Toyohara, Alauddin and Balzarini synthesized and evaluated several analogues with 18 F or 19 F attached to N3-alkyl side chains (82–87) [27,28,8689,101]. Balzarini et al observed that 83 was a relatively poor inhibitor of thymidine phosphorylation by TK1 [28].…”
Section: Non-boronated N3-substituted Thymidine Analoguesmentioning
confidence: 99%
“…An unnatural analog of FMAU, [ 18 F]‐ l ‐FMAU, was recently developed and was shown to have efficacy in PET imaging of tumor proliferation . N 3 ‐Substitued TdR analogs have been synthesized, radiolabeled, and studied in limited experiments …”
Section: Biochemical Substrates Specific For Thymidine Kinase Type 1 mentioning
confidence: 99%
“…A number of N 3 ‐substitued TdR analogs have been synthesized and radiolabeled with 18 F to assess their efficacy for PET imaging of tumors . Previously, a series of N 3 ‐substituted TdR analogs carrying a carboranylalkyl moiety at the N 3 ‐position with various spacer lengths was developed and drew attention in boron neutron capture therapy .…”
Section: Biochemical Substrates Specific For Thymidine Kinase Type 1 mentioning
confidence: 99%
See 1 more Smart Citation